Intermetallic compound layer growth at the Interface between Sn-Ag and ENImAg surface finish - Mohamed Anuar, Rabiatul Adawiyah; Hamidin, Mohamad Shahrom; Osman, Saliza Azlina; Othman, Mohamad Hilmi (WARSE, 2020)
The growth of an intermetallic compound (IMC) can influence the behavior of solder joints. In this study, the different percentages of Ag in Sn-xAg (value x = 2.5 and 3.5 wt.%) solder alloy were involved along with ENImAg surface finish to reveal the solder joints reliability in term of IMC thickness, morphology and strength of solder joint under reflow and multiple reflows. The characterization and samples analysis were examined by OM and SEM/EDX. The observation revealed that the IMC of Sn-xAg/ENImAg which were formed on the interface were Ni3Sn4 and NiSn-P layer after multiple reflows soldering. The kinetic growth of each IMC was observed. It revealed that the layer of IMC was thicker as the reflow increased and became thinner with higher mass percentages of Ag. For solder joint strength, the fracture surface with ductile characteristics at the Sn-Ag/ENImAg interface, which indicated that an increase of Ag wt.% in the solder, increases the strength of the solder joint. Upon the revelation of these observations, the reliability of the solder joint is related to the reflow condition and mass percentages of the element in the solder alloy.